HYPERREALITY GAME ONLINE MENJERUMUSKAN GAMER MENJADI HYPER-LIFE? - Diah Meitikasari (Sosioglobal, 2022)
This paper aims to explore Jean Baudrillard's thoughts on hyperreality theory which is used as a tool to examine the phenomenon of gamer hyperreality. According to the author, this is important considering the growing online game and its impact not only on social but also on the death of its players. This paper uses a literature study approach with the main source of the work of Jean Baudrillard. This paper concludes that: first, online games are a tangible form for gamers. Second, humans as a concrete form have become abstract as a result of online games. Third, games are algorithm manipulation, and this is what causes gamers to become addicted to playing online games. Fourth, hyperreality gives birth to hyperlife for gamers so that they have neglected social responsibilities.Keywords: Hyperreality, game online, gamer, hyperlife